WebAssembly: Revolutionizing Web User Interface Development through Performance and Cross-Language Integration - Nikhil Sripathi Rao (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the transformative impact of WebAssembly on modern UI development, focusing on its fundamental role in bridging the performance gap between web and native applications. The article provides an in-depth analysis of WebAssembly’s technical architecture, performance characteristics, and security implications while exploring its practical applications in production environments. Through a detailed examination of cross-language development paradigms and framework integration patterns, this article demonstrates how WebAssembly enables developers to leverage multiple programming languages while maintaining web platform compatibility and security. The article investigation encompasses real-world implementations across various sectors, including graphics processing, financial services, and interactive web applications, providing empirical evidence of WebAssembly’s capacity to deliver near-native performance within the browser environment. The article also addresses emerging trends and challenges in WebAssembly development, offering insights into future directions and potential solutions. The article findings indicate that WebAssembly represents a significant advancement in web development technology, enabling a new generation of high-performance web applications while maintaining the security and platform independence that characterize the modern web platform.